MEDICAL DRUGS IN COUGH TREATMENT IN CHILDREN: COMPARATIVE CHARACTERISTICS - M. I. Petrovskaya ("Paediatrician" Publishers LLC, 2013)
Cough is one of the most common symptoms of respiratory tract diseases, especially - of infectious etiology, various types of airways and pleura disorders. Cough can accompany cardiovascular, gastrointestinal and metabolic disorders. Correct interpretation of cough and establishment of its cause can contribute to appropriate treatment of underlying diseases.. Phytotherapy in cough treatment is very spread in Russia. But administration of such drugs requires pathogenesis-based approach. The article deals with the issue of herbal drugs of secretomotoric expectorant group, allowed to use in children older than 2 years. The author gives comparative characteristics of these drugs, covers pharmacological action of the drugs components and discusses the questions of their efficacy and safety.